2022
DOI: 10.1002/humu.24365
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific genotype–phenotype correlations among USH2A‐related disorders in the RUSH2A study

Abstract: We assessed genotype–phenotype correlations among the visual, auditory, and olfactory phenotypes of 127 participants with Usher syndrome (USH2) (n =80) or nonsyndromic autosomal recessive retinitis pigmentosa (ARRP) (n = 47) due to USH2A variants, using clinical data and molecular diagnostics from the Rate of Progression in USH2A Related Retinal Degeneration (RUSH2A) study. USH2A truncating alleles were associated with USH2 and had a dose‐dependent effect on hearing loss severity with no effect on visual loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…This is in keeping with previous reports that show patients with Usher syndrome type 2A develop symptoms at a younger age compared to patients with NS-ARRP associated with USH2A mutations (median age, 15 years vs. 25 years; p < 0.001) [ 3 ]. The mean age of first ocular symptoms in patients with USH associated with USH2A in our cohort is similar to that reported in the literature [ 1 , 3 , 19 , 29 ] and the recent RUSH2A study also found that the age of symptom onset in NS-ARRP patients was 31.8 years compared to 18.4 years in USH2A patients [ 12 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is in keeping with previous reports that show patients with Usher syndrome type 2A develop symptoms at a younger age compared to patients with NS-ARRP associated with USH2A mutations (median age, 15 years vs. 25 years; p < 0.001) [ 3 ]. The mean age of first ocular symptoms in patients with USH associated with USH2A in our cohort is similar to that reported in the literature [ 1 , 3 , 19 , 29 ] and the recent RUSH2A study also found that the age of symptom onset in NS-ARRP patients was 31.8 years compared to 18.4 years in USH2A patients [ 12 ].…”
Section: Discussionsupporting
confidence: 89%
“…Colombo et al similarly reported worse visual acuities in patients with syndromic USH2A and visual acuity was also worse in patients with more severe USH2A variants [ 30 ]. The RUSH2A trial also reported that their USH2A patients with NS-ARRP had greater preservation of visual fields compared to patients with USH after adjustment of disease duration and age of enrolment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations